Temporal dynamics of coarticulatory cues to prediction - Lulaci, Tugba; Söderström, Pelle; Tronnier, Mechtild; Roll, Mikael (Frontiers in Psychology, 2024)
The temporal dynamics of the perception of within-word coarticulatory cues remain a subject of ongoing debate in speech perception research. This behavioral gating study sheds light on the unfolding predictive use of anticipatory coarticulation in onset fricatives. Word onset fricatives (/f/ and /s/) were split into four gates (15, 35, 75 and 135 milliseconds). Listeners made a forced choice about the word they were listening to, based on the stimulus gates. The results showed fast predictive use of coarticulatory lip rounding during /s/ word onsets, as early as 15 ms from word onset. For /f/ onsets, coarticulatory backness and height began to be used predictively after 75 ms. These findings indicate that onset times of the occurrence and use of coarticulatory cues can be extremely fast and have a time course that differs depending on fricative type.